The Role of Institutional Pressure and Dynamic Capabilities in Promoting Energy Efficiency Practices: Evidence from the Moroccan Manufacturing Sector - Bensouda, Mehdi; Benali, Mimoun (International Journal of Energy Economics and Policy, 2023)
As most world countries, Morocco is facing energy challenges related to the increase in energy consumption resulting from the population growth. Thus, energy efficiency practices are increasingly considered as a priority for the country. Manufacturing companies are pivotal elements to improve energy efficiency. Despite the ambitious Moroccan strategy for energy efficiency, a considerable number of manufacturing companies are lagging in terms of energy efficiency. By drawing on institutional theory, we construct a research model that aims to assess the effect of institutional pressure on energy efficiency practices. Importantly, we explore the mediating role of dynamic capabilities between institutional pressure and energy efficiency practices. Our research model was empirically tested using survey data collected from 193 manufacturing companies located in four different regions of Morocco. Results show that companies’ dynamic capabilities positively influence companies’ energy efficiency practices. Coercive pressure is not positively related to dynamic capabilities, whereas normative and mimetic pressure are positively related to dynamic capabilities. Coercive pressure does not directly influence energy efficiency practices and does not influence energy efficiency practices through the mediation of dynamic capabilities. Normative and mimetic pressure directly influence energy efficiency practices and influence energy efficiency practices through the mediation of dynamic capabilities.